Biorefinery strategies: exploring approaches to developing forest-based biorefinery activities in British Columbia and Ontario, Canada. Issue 5 (28th May 2017) - Blair, M. Jean; Cabral, Laura; Mabee, Warren E.
ABSTRACT: Forest biorefineries can help revive and diversify a struggling Canadian forest sector while enabling Canada's transition to an advanced bioeconomy. Two distinct approaches to biorefining – centralised and distributed – are defined and assessed to determine their suitability for application in this sector. A proposed set of critical capacities required for the forest industry to transition to a biorefining business model form the basis of a comparison between the centralised and distributed approach. The potential implementation of each approach in the provinces of British Columbia (BC) and Ontario is assessed based on existing forestry infrastructure and available forest fibre. It is found that biorefinery development is likely to follow a distributed pathway in Ontario. In BC, the distributed model may also be attractive, but two locations are identified where a centralised approach may be successfully implemented.